Emerging from the shadows: exploring registered nurses' experiences of work-based learning projects from a Habermasian perspective - Roberts, Maggie (2020)
Within the context of the United Kingdom National Health Service (UKNHS) in the twenty-first century, there is pressure on the nursing profession to change working practices to suit a competitive market of healthcare. Historically, nurses trained in the UKNHS perceived themselves as working in an environment where public service values guided their activity. The research reported in this thesis used work-based learning (WBL) projects as a site in which to explore the conflicts that arise when these values clash with those of marketisation. The findings revealed that the nurses’ lack of political awareness and their restricted power hindered their attempts to bring about change through their projects. As an educational approach to the professional development of nurses, WBL has been lauded by nurse educators as personally empowering and facilitating nurses to become leaders (Swallow, Hall and English, 2006; Manley, Titchen and Harding, 2009; Stupans and Owen, 2010; Quick, 2010; Williams, 2010; Marshall, 2012). In this thesis Habermas’s Theory of Communicative Action (1984, 1987) is used as a lens to investigate the healthcare workplace as a learning environment and to assess the contribution of WBL to the professional development of nurses. The Habermasian concepts of the ‘life-world’, ‘systems,’ ‘colonisation’ and ‘communicative reason’ are used to examine the learning experience. Interviews with ten experienced nurses who had undertaken work-based projects showed that within the nursing ‘life-world’ the nurse-participants were motivated by their relationships with patients and wanted to enhance care in a collaborative way, but the political, economic and social ‘systems’ around them presented challenges that impacted on their learning and the efficacy of workplace projects. Ideological and practical challenges were presented by the conflicts that arose during the implementation of their project work. In this thesis I show how the nursing ‘life-world’ was shaped by socio-political influences that constrained the nurses’ abilities to improve services. The nurses’ reflections on their projects revealed both the hierarchical nature of their existing ‘life-world’ and the ‘colonising’ effect of business ‘systems.’ Not understanding the political and economic forces shaping their work, left these nurses at a disadvantage or ‘in the dark’ when knowing how to influence service developments. Habermas’s concept of ‘communicative reason’ was used to analyse the WBL interactions reported and to explore how the educational support offered in WBL contributed to nurses’ empowerment. As a vehicle for professional development WBL was found to have strengths and weaknesses: while it encouraged leadership development, it did not prepare the nurse-participants adequately for the challenges of the work setting. It is argued that a focus on socio-political awareness and communicative reasoning would enhance the nurses’ power. By increasing self-awareness and self-determination; facilitating a questioning of influences on work environments and promoting collaborative working nurses could emerge from the shadows and become influential in the workplace.